Digital Identity and the Blockchain: Universal Identity Management and the Concept of the “Self-Sovereign” Individual - Zwitter, Andrej J.; Gstrein, Oskar J.; Yap, Evan (Frontiers in Blockchain, 2020)
While ‘classical’ human identity has kept philosophers busy since millennia, ‘Digital Identity’ seems primarily machine related. Telephone numbers, E-Mail inboxes, or Internet Protocol (IP)-addresses are irrelevant to define us as human beings at first glance. However, with the omnipresence of digital space the digital aspects of identity gain importance. In this submission, we aim to put recent developments in context and provide a categorization to frame the landscape as developments proceed rapidly. First, we present selected philosophical perspectives on identity. Secondly, we explore how the legal landscape is approaching identity from a traditional dogmatic perspective both in national and international law. After blending the insights from those sections together in a third step, we will go on to describe and discuss current developments that are driven by the emergence of new tools such as ‘Distributed Ledger Technology’ and ‘Zero Knowledge Proof’. One of our main findings is that the management of digital identity is transforming from a purpose driven necessity towards a self-standing activity that becomes a resource for many digital applications. In other words, whereas traditionally identity is addressed in a predominantly sectoral fashion whenever necessary, new technologies transform digital identity management into a basic infrastructural service, sometimes even a commodity. This coincides with a trend to take the ‘control’ over identity away from governmental institutions and corporate actors to ‘self-sovereign individuals’, who have now the opportunity to manage their digital self autonomously. To make our conceptual statements more relevant, we present several already existing use cases in the public and private sector. Subsequently, we discuss potential risks that should be mitigated in order to create a desirable relationship between the individual, public institutions, and the private sector in a world where self-sovereign identity management has become the norm. We will illustrate these issues along the discussion around privacy, as well as the development of backup mechanisms for digital identities. Despite the undeniable potential for the management of identity, we suggest that particularly at this point in time there is a clear need to make detailed (non-technological) governance decisions impacting the general design and implementation of self-sovereign identity systems.